Firm Specific Attributes and Voluntary Disclosure information: Evidence from listed manufacturing companies in Nigeria - Agbaje, Taiwo; Josiah, Mary (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
Abstract The study examined the effect of firm specific attributes and voluntary disclosures of listed manufacturing companies in Nigeria for period of 10 years (2014 to 2023). The study adopted the longitudinal research design, secondary data was sourced from the audited annual report of sampled 46 manufacturing companies. The fixed effect estimation technique revealed that firm size has positive effect (0.082) which is statistically significant (p=0.017) at 1% level; firm leverage has positive effect (5.05) and it is statistically insignificant (p=0.988) at 5%; firm profit has a negative effect (-0.000) and it is statistically insignificant (p=0.177) at 5%; and board independence has negative effect (0.002) and it is statistically significant (p=0.001) at 5%. The study concluded that firm size is one of the factors that increases voluntary disclosure information. The study recommended that the manufacturing should work towards increase in the size of their firm in order to increase the level of their voluntary disclosure information.